Study of the Boson Peak and Fragility of Bioprotectant Glass-Forming Mixtures by Neutron Scattering. (19th September 2013) - Migliardo, F.; Magazù, S.; Gonzalez, M. A.; Mondelli, C.
Abstract : The biological relevance of trehalose, glycerol, and their mixtures in several anhydrobiotic and cryobiotic organisms has recently promoted both experimental and simulation studies. In addition, these systems are employed in different industrial fields, such as pharmaceutical and cosmetic industries, as additives in mixtures for cryopreservation and in several formulations. This review article shows an overview of Inelastic Neutron Scattering (INS) data, collected at different temperature values by the OSIRIS time-of-flight spectrometer at the ISIS Facility (Rutherford Appleton Laboratory, Oxford, UK) and by the IN4 and IN6 spectrometers at the Institut Laue Langevin (ILL, Grenoble, France), on trehalose/glycerol mixtures as a function of the glycerol content. The data analysis allows determining the Boson peak behavior and discussing the findings in terms of fragility in relation to the bioprotective action of trehalose and glycerol.